A New Class of Harmonic Univalent Functions Defined By an Integral Operator (Global Journal of Science Frontier Research, 2012)
We define and investigate a new class of harmonic univalent functions defined by Salagean integral operator. We obtain coefficient inequalities and distortion bounds for the functions in this class.
Keywords: Integral operator; harmonic univalent functions; distortion inequalities